2017
DOI: 10.1039/c7md00409e
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel N-acetylcysteine derivatives for the treatment of hepatocellular injury

Abstract: New anti-hepatocellular injury drugs with better curative effects and fewer side effects are urgently needed at present. In this study, a series of novel -acetylcysteine (NAC) derivatives were designed, synthesized and biologically evaluated for their anti-hepatocellular injury activities against two different cell models. In the biological evaluation against hydrogen peroxide (HO)-induced LO2 hepatocytes, half of the target compounds exhibited moderate to potent activities in improving the model cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…While the literature does not provide prior in vitro examples for NACA, one study with an epithelial Caco‐2 barrier model has reported P app for NAC below their assay detection limit (≈5−10 nm s −1 ). [ 58 ] Compared to hiBMEC, Caco‐2 are typically leakier (e.g., 13 vs <2.5 nm s −1 for sodium fluorescein). [ 8,59 ] Taken together, this may indicate that indeed NACA features higher BBB permeability than NAC.…”
Section: Resultsmentioning
confidence: 99%
“…While the literature does not provide prior in vitro examples for NACA, one study with an epithelial Caco‐2 barrier model has reported P app for NAC below their assay detection limit (≈5−10 nm s −1 ). [ 58 ] Compared to hiBMEC, Caco‐2 are typically leakier (e.g., 13 vs <2.5 nm s −1 for sodium fluorescein). [ 8,59 ] Taken together, this may indicate that indeed NACA features higher BBB permeability than NAC.…”
Section: Resultsmentioning
confidence: 99%
“…While the literature does not provide prior examples for NACA, one study with an epithelial Caco-2 barrier model has reported P app for NAC below their assay detection limit (~5-10 nm s -1 ). [51] Compared to hiBMEC, Caco-2 are typically leakier (e.g., 13 versus <2.5 nm s -1 for sodium fluorescein). [9,52] Taken together, this may indicate that indeed NACA features higher BBB permeability than NAC.…”
Section: Resultsmentioning
confidence: 99%
“…While the literature does not provide prior examples for NACA, one study with an epithelial Caco-2 barrier model has reported Papp for NAC below their assay detection limit (~5−10 nm s −1 ). [51] Compared to hiBMEC, Caco-2 are typically leakier (e.g., 13…”
Section: Verification Of Dosage Levelsmentioning
confidence: 99%
“…Konduktivitas listrik pada larutan H3PO4 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) Grafik 1. Konduktivitas Listrik pada Larutan H3PO4 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Konduktivitas hidrolik Parameter atau ukuran yang dapat menggambarkan kemampuan tanah dalam melewatkan air disebut sebagai konduktivitas hidrolik (Hydraulic Conductivity) (1,2,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71) . Tingkat kemampuan tanah untuk melewatkan air sangat dipengaruhi oleh kadar air tanah.…”
Section: Persen Massaunclassified